A Secure Communication Scheme Based on Equivalent Interference Channel Assisted by Physical Layer Secret Keys. (21st October 2020) - Hu, Xiaoyan; Jin, Liang; Huang, Kaizhi; Ma, Keming; Song, Changcheng; Xiao, Shuaifang
Abstract : Due to the channel estimation error, most of the physical layer secret key generation schemes need information reconciliation to correct error key bits, resulting in reduced efficiency. To solve the problem, this work proposes a novel secure communication scheme based on a equivalent interference channel. Different keys generated from imperfect channel state information are directly applied to signal scrambling and descrambling, which is equivalent to the process of a signal passing through an interference channel. Legitimate communication parties can reduce interference with the help of similar keys and channel coding without sending additional signals, while the eavesdropper channel is deteriorated due to the spatial decorrelation. For this kind of schemes, we first establish a discrete memoryless broadcast channel model to derive the expressions of bit error rate (BER), channel capacity, and security capacity for performance analysis. Simulation results verify the derivations that the proposed scheme achieves secure communication with a correlated eavesdropping channel and has a higher upper bound of transmission rate. Furthermore, we design a new metric to evaluate the efficiency and the result shows that the proposed scheme has superior performance on error reconciliation efficiency, despite its slight increase in BER.